Enhancing the sensitivity and selectivity of salbutamol detection using reduced graphene oxide combined with molecularly imprinted polymers (RGO/MIP) - Dalawan Limthin; Piyawan Leepheng; Korakot Onlaor; Benchapol Tunhoo; Annop Klamchuen; Thutiyaporn Thiwawong; Darinee Phromyothin (Japanese Journal of Applied Physics, 2022)
Abstract In this study, to enhance the selectivity and sensitivity of salbutamol detection performed by a carbon plate electrode, the electrode was modified using a novel molecularly imprinted polymer (MIP) combined with reduced graphene oxide (RGO). The RGO/MIP combination was prepared by the polymerization of methacrylic acid as a monomer using salbutamol as a template. The surface morphologies of the modified electrodes were studied using field-emission scanning electron microscopy (FE-SEM), and their performance was tested by an electrochemical technique that investigated both the cyclic voltammetry (CV) and amperometry (AMP) modes. The performance of the modified RGO/MIP electrode was compared with that of an MIP electrode, in which the RGO/MIP electrode was demonstrated to have 4.16 nA/ppm of sensitivity, more than the 0.91 nA/ppm of the MIP electrode. The limit of detection (LOD) of the RGO/MIP electrode, which was 0.83 ppm, was lower than that of the MIP electrode. Moreover, the RGO/MIP electrode’s dynamic range extended from 1 to 1000 ppm, and it exhibited consistency, repeatability, a fast response, and high selectivity for salbutamol detection.
Keywords: Pharmacological Effects and Assays; Analytical chemistry methods development; Analytical Chemistry and Sensors